Analisis Peran Kompetensi Pedagogik Guru SD Pasca Program PPG dalam Pembelajaran Ditinjau dari Faktor Kepemimpinan Transformasional dan Budaya Sekolah - Biassari, Icha; Andrijati, Noening; Wijayati, Nanik; Avrilianda, Decky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role of pedagogical competence of elementary school teachers after participating in the Teacher Professional Education Program (PPG) in the learning process by considering the influence of transformational leadership and school culture. Pedagogical competence is understood as the ability of teachers to design lesson plans, implement teaching and learning activities, and conduct effective learning assessments. Although teachers have participated in professional training programs, the implementation of these competencies is also influenced by the conditions and support of the school environment. This research uses a qualitative approach with a descriptive research type. The research informants consist of elementary school teachers who have completed the PPG program and school principals. Data collection was carried out through interviews, observations of the learning process, and documentation studies related to learning activities and instructional documents. Furthermore, the data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing systematically. The results show that teachers who have completed the PPG program demonstrate improved abilities in preparing learning tools, managing classrooms, and conducting learning evaluations. In addition, the transformational leadership of school principals plays a role in providing motivation and support for teachers to continuously improve their professional competence. A positive school culture also encourages collaboration, innovation, and improvement in the quality of learning. Therefore, leadership and school culture are important factors in optimizing teachers’ pedagogical competence in the learning process.